Pengaruh Jumlah Angkatan Kerja dan Investasi terhadap Pendapatan Asli Daerah - Tianto, Reza (Fakultas Ekonomi Universitas Samudra, 2022)
The purpose of this study is to analyze the effect of the number of labor force and investment on Regional Original Income Revenue (PAD). Provincial PAD in Indonesia has different figures for each province. Every year the PAD figure fluctuates and forms a certain pattern for each province. The number of labor force and investment is estimated to affect the amount of PAD figure. The research used data from 34 provinces in Indonesia taken from the Central Statistics Agency in 2020, and analyzed using the multiple linear regression method. The results found that the number of labor force and investment had a significant and positive effect on PAD. Based on the analysis of determination, it is found that the number of labor force and investment has a relatively large contribution to explain fluctuations in PAD, although there are still a number of other independent variables that are not included in this research model.